Analysis of Function Improvements Due To Changes In Core Zone Material Based on Value Engineering at Urugan Batu Dam - Dhania Kusumastuti; Agus Suroso (Publikasi Indonesia, 2023)
An embankment dam is a large artificial embankment made by placing and compacting various compositions of soil, sand, clay or rock. One of the rock fill dams located in the Buleleng Regency, Bali Province, namely the Tamblang Dam which is planned to be utilized to meet the raw water needs in the Buleleng Regency in particular and the Bali Province of 510 liters/second, irrigates irrigated rice fields in Bungkulan and in Bulian with an area of 588 Ha, as a micro hydro power generator of 2 x 269 MW, as well as other uses for flood control and tourism. At first the Tamblang Dam was a rock fill dam with an upright core made of clay material. After conducting test pits at 30 borrowed areas and soil investigations at an independent laboratory, the volume of the core zone material according to specifications cannot meet the needs of the core material. There are alternative solutions to the problem, namely bringing in core zone material from outside the project site or changing the original clay core design into an asphalt concrete core. This study applies the Value Engineering (VE) method in which an increase in function at a fixed cost or an increase in function will be obtained by reducing costs or reducing costs for a fixed function or increasing costs and increasing functions.